2021
DOI: 10.3390/toxins13080569
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polygenic Risk Score and Bacterial Toxins at Screening Colonoscopy with Colorectal Cancer Progression: A Multicenter Case-Control Study

Abstract: Colorectal cancer (CRC) is a leading cause of cancer death worldwide, and its incidence is correlated with infections, chronic inflammation, diet, and genetic factors. An emerging aspect is that microbial dysbiosis and chronic infections triggered by certain bacteria can be risk factors for tumor progression. Recent data suggest that certain bacterial toxins implicated in DNA attack or in proliferation, replication, and death can be risk factors for insurgence and progression of CRC. In this study, we recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Several modifications induced by CNF1 are, in fact, reminiscent of a procarcinogenic potential [111,112]. In recent years, studies have been carried out to corroborate this hypothesis [21,113], but the subject of study is still in its infancy.…”
Section: Discussionmentioning
confidence: 99%
“…Several modifications induced by CNF1 are, in fact, reminiscent of a procarcinogenic potential [111,112]. In recent years, studies have been carried out to corroborate this hypothesis [21,113], but the subject of study is still in its infancy.…”
Section: Discussionmentioning
confidence: 99%
“…Several bacterial pathogens can produce enzymatically active protein toxins that can directly attack and damage DNA or become involved in essential host cell signaling pathways that direct cell proliferation, apoptosis, and inflammation [ 68 ]. The E. coli colibactin and cytolethal distending toxin (CDT) are significant examples of bacterial toxins able to induce mutations and genome instability, whereas the Bacteroides fragilis toxin, the E. coli Cif and cytotoxic necrotizing factor 1 (CNF1), the Fusobacterium nucleatum FadA, and the Salmonella AvrA are prototypes of toxins that engage signaling pathways, ultimately leading to transformation [ 68 , 69 ]. Chronic inflammation can contribute to colorectal cancer via several mechanisms, including the induction of the epithelial–mesenchymal transition (EMT), a process involved in metastasis, invasion, and cancer progression.…”
Section: Microbiota In Lung Cancermentioning
confidence: 99%
“…Although, in in vitro experiments, CIF inhibited the proliferation of cancer cells and eventually led to apoptosis, where new epidemiological data confirm the role of CIF in carcinogenesis. In a recent multicenter case-control study, an association of the cif gene with precancerous lesions—intestinal polyps or adenomas—was found that can occur in the early stages of carcinogenesis, and this association has been assessed as a statistically significant risk factor [ 37 ].…”
Section: Cyclomodulins—cifsmentioning
confidence: 99%